Effectiveness of E-Worksheets on Problem-Solving Skills: A Study of Students' Self-Directed Learning in the Topic of Ratios - Harini, Esti; Nurul Islamia , Almira; Kusumaningrum, Betty; Singgih Kuncoro, Krida (International Journal of Mathematics and Mathematics Education (IJMME), 2023)
This study investigates the effectiveness of E-Worksheets in enhancing students' problem-solving skills, with a specific focus on self-directed learning, in the topic of ratios. The research examines the impact of technology-based learning tools on students' ability to solve problems and explores the relationship between self-directed learning and problem-solving abilities. The study employs a control group design, comparing the performance of students using E-Worksheets with those in a control group. The findings indicate that the use of E-Worksheets significantly improves students' problem-solving skills compared to the control group. Moreover, the analysis reveals a positive association between students' level of self-directed learning and their problem-solving abilities. These findings support the integration of technology in the learning process to create interactive and engaging experiences that foster problem-solving skills. The study emphasizes the importance of cultivating students' self-directed learning and recommends strategies for educators to promote independent problem-solving and collaboration among students. The implications of this research contribute to the understanding of the role of E-Worksheets and self-directed learning in enhancing problem-solving skills and provide valuable insights for future research and educational practices.